Interdisciplinary Innovations in Biomedical and Health Informatics Graduate Education - Demiris, G. (Methods of Information in Medicine, 2007)
Objectives: Biomedical and health informatics (BHI) is a rapidly growing domain that relies on the active collaboration with diverse disciplines and professions. Educational initiatives in BHI need to prepare students with skills and competencies that will allow them to function within and even facilitate interdisciplinary teams (IDT). This paper describes an interdisciplinary educational approach introduced into a BHI graduate curriculum that aims to prepare informatics researchers to lead IDT research.Methods: A case study of the “gerontechnology” research track is presented which highlights how the curriculum fosters collaboration with and understanding of the disciplines of Nursing, Engineering, Computer Science, and Health Administration. Gerontechnology is a new interdisciplinary field that focuses on the use of technology to support aging. Its aim is to explore innovative ways to use information technology and develop systems that support independency and increase quality of life for senior citizens. As a result of a large research group that explores “smart home“ technologies and the use of information technology, we integrated this new domain into the curriculum providing a platform for computer scientists, engineers, nurses and physicians to explore challenges and opportunities with our informatics students and faculty.Results: The interdisciplinary educational model provides an opportunity for health informatics students to acquire the skills for communication and collaboration with other disciplines. Numerous graduate and postgraduate students have already participated in this initiative. The evaluation model of this approach is presented.Conclusion: Interdisciplinary educational models are required for health informatics graduate education. Such models need to be innovative and reflect the needs and trends in the domains of health care and information technology.
Keywords: Education; interdisciplinary communication; educational measurement; informatics